Supporting Symbolic and Cognitive Development in Early Childhood through Pop-Up Book Learning Media - Sindi Usman; Shofiyanti Nur Zuama; Sita Awalunisah; Andi Agusniatih (GENIUS: Indonesian Journal of Early Childhood Education, 2025)
This study aims to develop a Pop-Up Book learning media to stimulate cognitive abilities in early childhood education, particularly in recognizing letters, shapes, and symbols. The research employed a Research and Development (R&D) approach using the ADDIE model, encompassing analysis, design, development, implementation, and evaluation stages. The subjects consisted of 15 children in Group B1 at Alkhairaat Tondo Kindergarten. Data were collected through observation, interviews, documentation, and questionnaires to assess needs, feasibility, and children’s responses to the developed media. Expert validation results indicated a very high level of feasibility, with scores of 98.3% from media experts and 96.6% from material experts. Classroom implementation showed positive engagement, with 60% of children developing cognitive abilities as expected and 40% beginning to show improvement. These findings suggest that the developed Pop-Up Book media is feasible, engaging, and has potential to support cognitive development in early childhood learning contexts.